Weighted evidence combination based on improved conflict factor. (2nd January 2016) - Xing, Xiaochen; Cai, Yuanwen; Zhao, Zhengyu; Cheng, Long
Abstract: The combination of heavy conflict evidence based on D-S evidence theory always has flaws. Research on a combination of conflict evidence at home and abroad is summarized and analyzed in detail, and the conclusion can be drawn that a modified evidence method of conflict evidence is more useful. Obtaining an effective measure of evidence conflict is the first step of conflict evidence combination. The existing conflict measure methods are summarized and the main problem of those methods is analyzed. An improved evidence conflict measure factor called Mconf is put forward based on previous research of conflict evidence combination. Mconf is mainly built up with modified evidence distance called mdBPA and combination conflict called k. A weighted evidence combination method based on Mconf is proposed. A typical case is used to validate the proposed method, and combination results show the proposed method is effective.